NASIHAT PENDIDIKAN ANAK PERSPEKTIF IMAM AL-GHAZALI KAJIAN KITAB AYYUHAL WALAD - Romaida, Romaida; Robi'ah, Robi'ah; Darwis, Muhajir (Jurnal Ilmiah Pendidikan dan Keislaman, 2023)
These adults, the majority of students are still indifferent when given advice. This is contrary to the principles of Islamic teachings which require Muslims to be kind in accepting Islamic teachings. This study aims to determine educational advice for students from the perspective of Imam Al-Ghazali in the translation of the book Ayyuhal Walad and its relevance to current education. This type of research is library research (Library Research). For students, advice on choosing appropriate educational material to learn. Advice on choosing an educational method Imam Al-Ghazali's thought have relevance to current education, where students in studying should set a goal of studying, namely getting closer to Allah SWT. And students need knowledge to be able to achieve these goals.